(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Avascular necrosis and non-union are common but when the neck of femur fracture in adult is neglected, the chances of complications rises. Among various treatment options, we report the outcome of free fibular strut graft along with two cannulated hip screws in neglected fracture neck of femur. Methods: The outcome analysis of ‘fibular strut graft and two cannulated hip screws’ was conducted in patients with fracture neck of femur who presented at least three weeks after the time of injury, during August 2008 to December 2017, at Lumbini Zonal Hospital and Lumbini Hospital Technical College, Butwal, Nepal. All adult patients aged 18 to 60 years were included. Outcome variables were healing of fracture (union, delayed union, non-union), avascular necrosis and Harris Hip Score (HHS). Results: Out of 20 fractures, 17 (85%) united uneventfully, 2 (10%) had delayed union and 1 (5%) nonunion. We had 3 (15%) avascular necrosis of femoral head. The HHS was excellent in 8 (40%), good in 4 (20%), fair in 6 (30%) and poor in 2 (10%). Conclusions: Fibular Strut graft with two hip screws resulted in fracture union and improved hip functions in patients with neglected fracture of neck of femur.